TINJAUAN KOMPETENSI GURU PLK TEKNIK BANGUNAN TAHUN AJARAN JULI-DESEMBER 2015 DI SMKN 1 TANJUNG RAYA - 1040-1059 , Deri Chandra (Universitas Negeri Padang, 2016)
ABSTRACT This research is purposed to reveal the competency of PLK teacher as voluntary-teacher in building engineering class academic period of Juli-December 2015 in SMKN 1 Tanjung Raya. Type of research was descriptive quantitative. Research population was all students at class X building engineering major year of school 2015/2016. Sample collection was conducted by total sampling where sample was amounted to 80 students.Research data was gathered by questionnaire, and then it was analyzed by descriptive analysis with SPSS version 17 software. Based on research finding, it can be reveal that competency of PLK teacher as voluntary-teacher in building engineering class academic period of Juli-December 2015 in SMKN 1 Tanjung Raya is in moderate category. Form each indicators of competency, which are pedagogic, personality, social and professional competencies, all of them are in moderate category. Keywords:pedagogic, personality, social and professional competencies.